MODEL PEMBELAJARAN NOVICK DENGAN MEDIA ORIGAMI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Ima Ni'matuzzahroh (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2020)
This study aims to describe the improvement of students 'critical thinking skills and to describe students' responses after the application of novick learning with origami media on the material of triangle of VII MTS class students. Hidayatul Mubtadiin Jenu academic year 2017/2018. This research is a Classroom Action Research (PTK). The subjects of the study were students of class VII MTs. Hidayatul Mubtadiin Jenu academic year 2017/2018 with a total of 27 students. Data in this research is data about student response questionnaire and critical thinking ability. The results obtained through the test of critical thinking skills cycle I is 56.67 and an increase in the results of the test of critical thinking skills cycle II is 65.74 and an increase in the results of the test of critical thinking skills cycle III is 82.22 it means the scores obtained have reached the target and the success criteria. The average percentage of students' positive responses was 88.75%.